Astragalus polysaccharide inhibits radiation-induced bystander effects by regulating apoptosis in Bone Mesenchymal Stem Cells (BMSCs). Issue 22 (16th November 2020) - Zhang, Yi-Ming; Zhang, Li-Ying; Zhou, Heng; Li, Yang-Yang; Wei, Kong-Xi; Li, Cheng-Hao; Zhou, Ting; Wang, Ju-Fang; Wei, Wen-Jun; Hua, Jun-Rui; He, Yun; Hong, Tao; et al.
ABSTRACT: The purpose of this study was to investigate the effects of astragalus polysaccharides (APS) on the proliferation and apoptosis of bone marrow mesenchymal stem cells (BMSCs) induced by X-ray radiation-induced A549 cells bystander effect (RIBE), and to explore their mechanisms. In this study, APS increased the reduced cell proliferation rate induced by RIBE and inhibiting the apoptosis of bystander cells. In terms of mechanism, APS up-regulates the proteins Bcl-2, Bcl-xl, and down-regulates the proteins Bax and Bak, which induces a decrease in mitochondrial membrane potential, which induces the release of Cyt-c and AIF, which leads to caspase-dependent and caspase-independent pathway to cause apoptosis. In addition, we believe that ROS may be the main cause of these protein changes. APS can inhibit the generation of ROS in bystander cells and thus inhibit the activation of the mitochondrial pathway, further preventing cellular damage caused by RIBE.